The Royalty Rights Fulfillment of the Song Creators on Musicians for Commercial Purposes - Marcellino Meidy, Salvatore (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Copyright is a crucial part of Intellectual Property Rights (can be called IPR). It is an exclusive right of the creator which arises automatically based on declarative principles after a creation is realized in real form. In this case, Dhani Ahmad Prasetyo or more familiarly known as Ahmad Dhani, is the leader of the Dewa 19 music band, which is one of the legendary bands in Indonesia. Since Ahmad Dhani's creative work is one of the souls of the music scene in Indonesia, he forbids anyone from being a professional singer to perform his work for conventional needs. This is also in force to the former vocalist of Dewa 19, namely Once Mekel. He officially pursues a solo career who often performs Dewa 19 songs for commercial purposes without giving royalties. This is a violation of the copyright of a song and must be fulfilled by royalties towards the creator of the original musical work, namely Ahmad Dhani as the creator of the work. The research method in this study used descriptive-analytic research with normative juridical methods. Copyright is regulated in Law Number 28 of 2014 concerning Copyright. Commercial use of copyrighted works without permission will be subject to sanctions in accordance with the provisions of Article 113 paragraph (2) of Law No. 28 of 2014, with a maximum imprisonment of 3 (three) years and/or a maximum fine of IDR 500.000.000 (five hundred million rupiah)